Bulyying behavior in vocational school students in west sumatra province - Zikry Latupasjana; Firman Firman (Indonesian Institute for Counseling, Education and Theraphy, 2023)
The problem of bullying in high school students in the province of West Sumatra, the problems in this study are what are the characteristics, factors, impacts, and efforts that have been made by tutors in overcoming bullying behavior? The method used is a descriptive research method that is used is survey research. The research data are counseling guidance teachers, students, classes, parents, and school principals. Data collection techniques, interviews, observation, and documentation. The intermediary data used are interview guidelines, observation results, larger, and absent research results, there are already internal ones such as wanting to be in power and being seen as great, high self-confidence, rebels against themselves, while external factors are, adoptive parents, social environment children, unable to accept what they are facing and encourage students to take bullying and have a negative impact. What has been done is to provide orientation services, individual counseling information services.